Pengaruh Budaya Organisasi Sistem Pengendalian Internal Dan Whistleblowing System Terhadap Pencegahan Fraud Dalam Pengelolaan Dana BumDes di Kecamatan Seririt - Candra Yani, Ni Putu Devy; Muliati, Ni Ketut; Andayani W, Rai Dwi (UNHI Press, 2025)
Fraud is a deviant and illegal act intentionally committed by individuals or groups to gain illegitimate benefits and can disadvantage others. Fraud prevention is an effort to prevent someone from engaging in potentially detrimental fraudulent activities. This study aims to determine the influence of Organizational Culture, Internal Control System, with also Whistleblowing System on Fraud Prevention in the management of Bumdes funds in Seririt District. This research was conducted in 11 BUMDes in the Seririt District, involving all BUMDes employees as the sample, totaling 70 individuals. The technique used was saturated sampling, and data analysis was performed using multiple linear regression methods. The results of this study indicate that Organizational Culture has a positive with also significant effect on fraud prevention. The Internal Control System has no effect on fraud prevention. The Whistleblowing System has a positive and significant effect on fraud prevention